Retroviroses, Toxoplasma gondii e Mycoplasma haemofelis em gatos errantes e felinos selvagens do zoológico de Belo Horizonte - MG - Anselmo Vasconcelos Rivetti Junior (2006)
A total of 19 samples from wild feline kept in captivity and 45 samples of two colonies from domestic stray cats (Felis catus) living in the campus of the Federal University of Minas Gerais and Belo Horizonte Zoo botanical garden were tested to establish the occurrence of the FIV,FeLV, Toxoplasma gondii and Mycoplasma haemofelis, and correlations between the occurrence of the diseases. The standardization of indirect immunofluorescence a (FAT), and imunoperoxidase on cellular monolayer (IPMA), was established and the application of thesewas carried through techniques compared with the polymerase chain reactions (PCR) for diagnostic the FIV